The Effect of Maternal Lullaby Singing, Affectionate Touch, and a Developmental Support Program on Comfort and Development in Premature Infants: A Randomized Controlled Trial - Funda Güler; Hüsniye Çalişir (Nursing Open, 2026)
ABSTRACT Aim Premature infants require interventions supporting comfort in the NICU and development after discharge. Therefore, this study examined the effects of maternal affectionate touch and lullaby singing on early comfort and of a developmental support programme on subsequent development. Design This randomized controlled experimental study included 57 premature infants in a neonatal intensive care unit: 27 in the intervention group and 30 in the control group. Methods Mothers in the intervention group provided lullaby singing and affectionate touch three times weekly for at least six 10‐min sessions. From 40 weeks' gestation, they implemented the developmental support programme, and infant development was assessed monthly for 3 months. The Premature Infant Comfort Scale and Developmental Support Programme Evaluation Form were used. Results Sex distribution was 8/19 girls/boys (29.6%/70.4%) in the intervention group and 16/14 (53.3%/46.7%) in the control group. Post‐intervention PICS scores were significantly lower in the intervention group in weeks 1, 2, and 4 ( p = 0.032, p < 0.001, and p = 0.047, respectively). At 1 month, social–emotional development ( p = 0.028), receptive language ( p = 0.005–0.009), productive language ( p = 0.002), and cognitive skills ( p = 0.004) were significantly higher in the intervention group. Receptive language at 2 months ( p = 0.028) and cognitive development at 3 months ( p = 0.033) also favoured the intervention group. In the BH‐FDR sensitivity analysis, only the Week 2 post‐intervention PICS difference (adjusted p = 0.012) and the first‐month PLS‐4 language finding (adjusted p = 0.040) remained statistically significant; the first‐month RLS‐3 finding was at the threshold of statistical significance (adjusted p = 0.050). Recommendations Maternal lullaby singing, affectionate touch, and developmental support may support comfort and early developmental follow‐up in premature infants; however, findings should be confirmed in larger studies with longer follow‐up. Patient or Public Contribution Mothers participated voluntarily and devoted sufficient time to each stage of the study. Trial Registration ClinicalTrials.gov identifier: NCT06191757